Skilled transitions: Digital training programmes as active labour market strategies in rural Portugal - Santos, A. S. R.; Bettencourt, L.; Roque, I.; Sousa, J. C. (Social Inclusion, 2025)
The transition from school to work in rural areas presents distinct challenges compared to urban environments, shaped by constraints on spatial mobility, limited employment opportunities, insufficient training provision, and cultural expectations, particularly concerning gender roles. The Covid‐19 pandemic and the expansion of remote work initially appeared to mitigate some of these barriers for digitally literate individuals with access to adequate infrastructure. However, many young people in rural areas lack the necessary digital skills and reliable internet connectivity to engage in remote employment, rendering digitalisation a potential obstacle rather than a facilitator of labour market integration. As a broader socio‐economic process, digitalisation has the potential to expand employment and training opportunities for young people. The pandemic accelerated the adoption of digital tools by public employment services, requiring significant adaptation by both service providers and users. In response, the Portuguese government has implemented a strategic framework encompassing training programmes and internships aimed at unemployed individuals with at least the minimum level of mandatory education. Despite the benefits of digitalised services, rural NEETs (persons not in employment, education, or training) frequently require more personalised, in‐person support to navigate labour market barriers effectively. This study adopts a comparative approach to examine two active employment programmes targeting unemployed young adults in rural Portugal: one centred on remote digital training and the other on digital upskilling through internships. Through document analysis and semi‐structured interviews with public employment services technicians, mentors, and NEETs aged 25–30, the findings underscore the relevance of these interventions, particularly for highly educated NEETs experiencing skills mismatches.